Identification of a novel Scn3b mutation in a Chinese Brugada syndrome pedigree: implications for Nav1.5 electrophysiological properties and intracellular distribution of Nav1.5 and Navβ3 - Fan, Jun; Wang, Shao-hua; Cao, Li-li; Li, Wei-jie; Sun, Shao-xi; Luo, Shao-ling; Pan, Yi-chao; Tan, Wen-liang; Wu, Tian-yuan; Liu, Zhen; Yu, Bing-bo (Frontiers in Cardiovascular Medicine, 2024)
Background: The Scn3b gene encodes for Navβ3, a pivotal regulatory subunit of the fast sodium channel in cardiomyocytes. However, its mutation status in the Chinese population suffering from Brugada Syndrome (BrS) has not been characterized, and the contributory pathophysiological mechanisms to disease pathology remain undefined. Methods and Results: A Scn3b (c.260C>T, p.P87L) mutation was identified in a patient with BrS of Chinese descent. Functional analyses demonstrated that sodium channel activation for the wild type, mutant samples, and co-expression of both commenced at -55mV and peaked at -25mV. The mutant group exhibited a notable reduction, approximately 60%, in peak sodium channel activation current (INa) at -25mv. The parameters for half-maximal activation voltages (V1/2) and slope factors (k) showed no significant differences when comparing wild type, mutant, and combined expression groups (P=0.98 and P=0.65, respectively). Additionally, no significant disparities were evident in terms of the steady-state sodium channel inactivation parameters V1/2 and k (with P values of 0.85 and 0.25, respectively), nor were there significant differences in the activation time constant τ (P = 0.59) and late sodium current density (P = 0.23) across the wild-type, mutant, and co-expressed groups. Confocal imaging and Western blot analysis demonstrated decreased plasma membrane localization of SCN3B and SCN5A in the P87L group. Computational simulations of cardiac action potentials suggested that SCN3B P87L can alter the morphology of the action potentials within the endocardium and epicardium while reducing the peak of depolarization. Conclusions: The pathogenic impact of the Scn3b P87L mutation predominantly originates from a reduction in peak INa activation current coupled with decreased cell surface expression of Nav1.5 and Navβ3. These alterations may influence cardiac action potential configurations and contribute to the risk of ventricular arrhythmias in individuals with BrS.